The Cost of Multiple Large Shareholders. Issue 2 (1st September 2015) - Cai, Charlie X; Hillier, David; Wang, Jun
Abstract : Previous research argues that large noncontrolling shareholders enhance firm value because they deter expropriation by the controlling shareholder. We propose that the conflicting incentives faced by large shareholders may induce a nonlinear relationship between the relative size of large shareholdings and firm value. Consistent with this prediction, we present evidence that there are costs to having a second (and third) largest shareholder, especially when the largest shareholdings are similar in size. Our results are robust to various relative size proxies, firm performance measures, model specifications, and potential endogeneity issues.